One-Pot Synthesis of Ag/Quaternary Ammonium Salt Co-Decorated Mesoporous Silica Nanoparticles for Synergistic Treatment of Cancer and Bacterial Infections - Zhang, Hanyuan; Xu, Jianxiang; Zhang, Xu; Wang, Teng; Zhou, Dairan; Shu, Wei; Zhao, Tingting; Fang, Weijun (Frontiers in Bioengineering and Biotechnology, 2022)
Developing drug delivery nanosystems with both anticancer and antibacterial effects is of great clinical value. Herein, we report a facile approach to synthesize Ag and quaternary ammonium salt (QAS) co-decorated mesoporous silica nanoparticles (MSNs), namely, Ag/QAS-MSNs, for synergistic treatment of cancer and bacterial infections. In vitro studies demonstrated that Ag/QAS-MSNs not only had a strong antibacterial activity against the bacterial pathogens but also could efficiently induce cancer cell death through an apoptotic pathway. Moreover, in vivo combination therapy with Ag and QAS in Ag/QAS-MSNs was also tested in a nude mouse tumor model, and a significant synergistic anticancer effect, which is superior to that obtained by therapy with Ag-MSNs or QAS-MSNs alone, was achieved. Such excellent anticancer and antibacterial activity of Ag/QAS-MSNs could be attributed to the synergistic effect of Ag ions and QAS. Thus, Ag/QAS-MSNs have a promising future as potent anticancer agents with high antibacterial performance.